History of previous bleeding and C-reactive protein improve assessment of bleeding risk in elderly patients (≥80 years) with myocardial infarction - Koller, Lorenz; Rothgerber, David-Jonas; Sulzgruber, Patrick; El-Hamid, Feras; Forster, Stefan; Wojta, Johann; Goliasch, Georg; Maurer, Gerald; Niessner, Alexander (Thrombosis and Haemostasis, 2015)
We aimed to assess whether the CRUSADE risk score represents a robust instrument for stratification of bleeding risk in elderly myocardial infarction (MI) patients (≥80 years) and further aimed to identify age-specific predictors of major bleeding events. Binary logistic regression models were applied to assess the effect of variables on the occurrence of bleeding events during hospital stay. Receiver operating characteristic (ROC) analysis was used to evaluate the discriminatory power. Out of 387 patients in the final study cohort, 74 patients (19.1 %) experienced a major bleeding event according to the definition of the International Society on Thrombosis and Haemostasis. The CRUSADE risk score demonstrated only a weak discriminatory power to predict bleeding in this group of patients (area under the ROC curve: 0.57 [0.51–0.65]; p=0.05). In the multivariate regression analysis, history of bleeding with an adjusted hazard ratio (HR) of 3.21(95 % confidence interval: 1.29–8.03, p=0.01) and C-reactive protein with an adjusted HR per increase of 10 mg/l of 1.05 (1.01–1.10) were independent predictors of major bleeding. Integration of both variables into the CRUSADE score demonstrated a significantly improved performance for bleeding as indicated by a significant increase in the ROC analysis (area under the curve: 0.64 vs 0.57; for comparison p<0.045), net reclassification index (35.6 0 %; p=0.006) and integrated discrimination increment (0.0242; p=0.02). In conclusion, bleeding history and C-reactive protein significantly improve the modest predictive power of the CRUSADE risk score in elderly patients with MI. These results point towards a specific risk profile for bleeding events in this high-risk group of patients.
Keywords: Aging; risk factors; ischaemic heart disease; inflammatory mediators